The Thoughts and Movements Dakwah of the Central MIUMI (Council of Intellectuals and Young Indonesian Ulama) in the Millennial Era. - Huwaidah, Helmi; Masran, Masran (Program Fakultas Dakwah dan Ilmu Komunikasi (FDIKOM), UIN Syarif Hidayatullah Jakarta, 2023)
Abstract The Indonesian Young Intellectuals and Ulama Council (MIUMI) is a forum for unifying intellectuals and scholars from various backgrounds. This institution was born as a response to the problems of religion, social, culture and government politics with intellectuality and Islam as a basis for thinking and moving in preaching. MIUMI Pusat is present in the millennial era of preaching against ideas that keep people away from the Al-Quran and Sunnah through the values of ahlus sunnah wal jama'ah. This research method is descriptivequalitative. Data collection techniques was obtained through observation, interviews, and documentation then analyzed with data collection techniques in the form of descriptive analysis. The theory used in this study refers to the thoughts of Dr. A Ilyas Ismail and Prio Hotman in the book, Schools of thought and the da'wah movement, dividing the four paradigms of da'wah, namely tabligh, community development, harakah, and culture. Keywords: Intellection, Movement, da’wah, MIUMI Pusat, paradigm